Diversity and functionality of soil prokaryotic communities in antarctic volcanic soils: insights from penguin-influenced environments - Segura, Diego; Jordaan, Karen; Díez, Beatriz; Tamayo-Leiva, Javier; Doetterl, Sebastian; id_orcid:0 000-0002-0986-891X; Wasner, Daniel; id_orcid:0 000-0002-3005-6203; Cifuentes-Anticevic, Jerónimo; Casanova-Katny, Angélica (Polar Biology, 2024)
ISSN:1432-2056 ISSN:0722-4060